Photocatalytic degradation of textile dye with titanium (IV) doped tungsten oxide nanoparticles - Shree H.K. Ranjini; Nidhi Pathak; Charu Lata Dube Dube (Zaštita Materijala, 2024)
Water pollution from textile industries is a major concern with respect to the availability of clean drinking water. The removal of textile (organic) dyes through photocatalytic degradation with pure WO3 and titanium (IV) doped tungsten oxide [Ti (IV)-WO3] nanospheres were studied under visible light. The WO3 and Ti (IV)-WO3 nanospheres were synthesized via microwave-assisted method at microwave power of 160 W for the duration of 20 mins. The as synthesised WO3 and Ti (IV)-WO3 nanospheres were characterized for their structural, microstructural, and spectroscopic properties by using powder X-ray diffraction (XRD), UV–Visible (UV-Vis) spectroscopy, Fourier-transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM) and High-resolution transmission electron microscopy (HR-TEM). The X-ray diffractograms confirmed the formation of highly pure WO3 and Ti (IV)-WO3 nanospheres. The average crystallite size of WO3 and Ti (IV)-WO3 nanospheres were calculated as 53.37 nm and 35.24 nm respectively using Debye Scherrer equation. The bandgap of Ti (IV)-WO3 was found to be decreased to 2.5 eV from 3.2 eV (WO3) respectively. It can be deduced that Ti (IV)-WO3 can be utilized as efficient visible light (λ>420 nm) driven photocatalyst as the bandgap was < 3 eV. The agglomerated spherical nanoparticles were seen for WO3 and Ti (IV)-WO3 in the HR-TEM images. The photocatalytic activity of textile dye was analyzed by UV-Vis spectrophotometer under visible light. The photocatalytic organic dye degradation was investigated. The enhanced photocatalytic activity of titanium (IV) doped tungsten oxide (10 wt%) was observed to be ~100% in 100 mins. This makes titanium (IV) doped tungsten oxide nanospheres, a potential nanomaterial for water purification.